The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmars.2023.1057502
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of midwater zooplankton along a productivity gradient in the Southeast Pacific

Abstract: The environmental regulation of planktonic food web structure is a key determinant for the efficiency of energy transfer through trophic levels, with direct implications for the amount of energy that is available to top-consumers and deep-sea communities. Yet, the complex trophic interplay between the different components of plankton communities under contrasting environmental conditions remains unresolved. Here, we present a comprehensive field study based on compound-specific isotope analysis of amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In the central Baltic Sea, the trigger for massive microbial systems are FNCs. However, massive microbial systems can also be caused by other factors such as eutrophication (Dähnke et al., 2008 ) or oxygen minimum zones (Fernández‐Urruzola et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the central Baltic Sea, the trigger for massive microbial systems are FNCs. However, massive microbial systems can also be caused by other factors such as eutrophication (Dähnke et al., 2008 ) or oxygen minimum zones (Fernández‐Urruzola et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the central Baltic Sea, the trigger for massive microbial systems are FNCs. However, massive microbial systems can also be caused by other factors such as eutrophication(Dähnke et al, 2008) or oxygen minimum zones(Fernández- Urruzola et al, 2023).In flounder, there were no significant differences or trends in the mean TPs between the two areas and the scatter of the individual TPs of flounder was lower than in cod. This suggests that flounder has a narrower diet composition and is decoupled from trophic lengthening in the pelagic food web.…”
mentioning
confidence: 98%
“…Zooplanktons play a crucial role in the transfer of energy at the secondary level in aquatic food webs, bridging the gap between autotrophs and heterotrophs [3]. Beyond their role in the complex balance of ecosystem components, zooplanktons serve as vital indicators of water quality and contamination, owing to their high sensitivity to environmental changes, Planktons, comprising a heterogeneous group of organisms, actively float and passively drift along the course of water currents in aquatic environments, making them invaluable indicators of environmental health [4].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the existence of these "scattered" changes (i.e., differential trophic isotopic fractionation of trophic amino acids) is the basis of the reworking index (ΣV, McCarthy et al 2007), which quantifies the heterotrophic microbial re-synthesis of the original autotrophic amino acid pool (Hannides et al 2013;Doherty et al 2021). A few studies have observed that this differential isotopic fractionation of glutamic acid and alanine in the microbial food web is further traceable in natural assemblages of zooplankton (Decima and Landry 2020;Fern andez-Urruzola et al 2023) and micronektonic fish (Bode et al 2021a,b). Based on these studies, the differential fractionation observed in alanine and glutamic acid through microbial metabolic processes can be used as an indicator of the contribution of bacteria and heterotrophic protists (i.e., number of trophic steps through protistan consumers) to the trophic position of metazoan consumers.…”
mentioning
confidence: 99%